Notes on the Accessory Flexor Carpi Ulnaris Muscle: A Rare Supernumerary Variation - Pires, Lucas Alves Sarmento; Machado, Graciele de Caro Reis; Fernandes, Rodrigo Mota Pacheco; Manaia, Jorge Henrique Martins; Champs, João Francisco Silva; Babinski, Marcio Antonio (Journal of Morphological Sciences, 2019)
Variations of the forearm muscles are well described in the literature. In spite of that, reports regarding the accessory flexor carpi ulnaris muscle are scarce due to its rarity. This muscle usually originates from the medial epicondyle of the humerus with the flexor muscle mass and inserts itself into the palmar aponeurosis or the pisiform bone together with the flexor carpi ulnaris muscle. Supernumerary and anomalous muscles of the anterior compartment of the forearm have been associated with ulnar nerve and artery compression. Furthermore, they may also mimic neuromas and soft tissue tumors. The study of supernumerary muscles is necessary, as they may be an option to tendon grafts and muscle flaps. The aim of this paper is to describe the presence of the accessory flexor carpi ulnaris muscle on the left forearm of a cadaver fixated in a phenol solution and discuss its clinical and anthropological significance.
Keywords: anatomic variations; flexor carpi ulnaris muscle; ulnar nerve; ulnar artery; anthropology